Employee Performance Based on Organizational Culture, Work Discipline, and Work Motivation (Case Study in Kelapa Lima District, Kupang City) - Krisman B Riwu Kore; Tien Yustini; Juhaini Alie (Institute of Computer Science (IOCS), 2022)
The purpose of this study is to analyze and prove the influence and contribution of organizational culture, discipline, and motivation to performance. This research was conducted for 5 months from February to June 2022 in the Sub-District Office and District Office in the Kelapa Lima District, Kupang City. This research is classified as quantitative research. The research population was 102 employees, which was determined by the sample of respondents using a saturated sample (non-probability sampling) so that the entire population became research respondents. The types of data used are primary and secondary data obtained by questionnaire, observation, and documentation techniques. Data analysis used multiple linear regression analysis. The results showed that the organizational culture variable had a positive and significant effect on employee performance because it had t-count > t-table (2.174 > 1.98397) in sig. 0.032 < 0.05. The discipline variable has a positive and significant effect on employee performance because the value of t-count > t-table (5.400 > 1.98397) in sig. 0.000 < 0.05 and the motivation variable has a positive and significant effect on employee performance because the t-count > t-table (2.014 > 1.98397) on sig. 0.047 < 0.05. Simultaneously, the variables of organizational culture, discipline, and motivation have a positive and significant effect on employee performance because of the F-count > F-table (166.220 > 2.45) in sig. 0.000 < 0.05. The contribution of each variable based on the highest value to the lowest value on employee performance is disciplined intelligence (54.5%), organizational culture (21.6%), and motivation (18.6%).